Workshop Pengembangan Instrumen Pembelajaran Berbasis Web Berbantuan OBS, Google Form, Quizizz dan Google Classroom di MGMP IPA Kabupaten Jombang - Juni Fitriyah, Isnanik; Sugiyanto; Yulianti, Erni; Pratiwi, Novida; Fajar Marsuki, Muhammad; Mualifah, Siti; Adi Widodo, Muhammad (Jurnal SOLMA, 2021)
Background: The current COVID-19 pandemic has led to school learning from offline to online. Basically, the main task of the teacher is to educate, teach, guide, direct, assess and evaluate students, where these tasks must be carried out by the teacher in any condition, especially the current COVID-19 pandemic. One of the most important media in online learning is the internet. MGMP is a forum for communication between subject teachers to improve teacher competence. Therefore, training on the development of web-based learning instruments was conducted for the IPA MGMP of Jombang Regency. Method: The stages of the activity include: 1) preparation, namely planning schedules and activities, 2) implementation, namely training carried out in the form of material delivery, discussion and presentation of participants, and 3) evaluation, namely the retrieval of response data of trainees for improvement of further activities. The trainees were 65 science teachers who were members of MGMP IPA Jombang Regency. Result: The first two days consisted of delivering learning video development materials using the OBS application, Google Form, Quizizz and Google Classroom, then participants working independently. Meanwhile, for the third day there is a presentation of the results of independent work by the participants and a review. Conclusion: implementation of this training has been good and has helped participants (science teachers) improve their skills in developing web-based learning instruments